Perjuangan Kedaulatan Finansial Indonesia melalui QRIS: Analisis Opini Publik terhadap Adopsi, Persepsi, dan Tantangan Komunikasi - Hasanah, Amalia; Ambari , Andina Rizki (VISA: Journal of Vision and Ideas, 2026)
This aims to public opinion regarding Indonesian strategic instrument for financial sovereignty and economic digitalization. Using a descriptive quantitative survey method, this study collected data from 107 respondents, the majority of whom reside in urban areas with high digital access. A structured online questionnaire was used to measure levels of understanding, convenience of use, security perceptions, and the challenges faced by the public. The findings indicate a very high level of knowledge and adoption of QRIS among respondents, with 89.7% stating they are very familiar with it and 96.3% using it due to its practicality. User satisfaction is also exceptionally high, with an average score of 4.52 out of 5. However, the primary challenge identified is the uneven availability of merchants, which 84.1% of respondents cited as the greatest obstacle. While there is general trust in its security, specific concerns about fraud persist. Respondents also demonstrated strong support for QRIS's role in reducing dependence on international payment networks (average score of 4.14 out of 5). This study concludes that while QRIS has been well-received, the expansion of merchant reach and ongoing security education are key to optimizing its full potential.